TRAFFIC IMPACT ANALYSIS OF ACCESSIBLE HUB AT KEBON KAWUNG TRAIN STATION AREA BANDUNG - AHMAD FAZA, HABBAB
Kebon Kawung Accessible Hub is an infrastructure created to overcome the problems that exist in the Kebon Kawung area of Bandung. These problems include; lack of network connectivity of pedestrian paths, disintegration between modes, and the lack of public space in the city of Bandung, especially in the Kebon Kawung area, Bandung. Accessible hub is one of many solution to create accessibility for pedestrians because it connects Jalan Kebon Kawung to Jalan Kebon Jati. In addition, the accessible hub is also a solution to the problem of intermodal disintegration by creating connecting access for three types of transportation modes, namely train, Bus Rapid Transit (BRT), and Light Rail Transit (LRT). The construction process until the operational period (in the next 5 years) of the accessible hub will certainly affect the traffic conditions around the Kebon Kawung area so that a traffic impact analysis is carried out which refers to the MKJI 1997, Minister of Transportation Regulation No. PM 96 of 2015, and Station Planning Standards and Guidelines, London Underground (2012). The analysis is done in the form of micro simulation modeling with PTV VISSIM software and vehicle generation estimation simulation using PTV VISUM software. From the analysis carried out, it was found that during the construction period there was no significant change in traffic conditions, while during the operational period there was an increase in the volume of vehicles on the Jl. Kebon Kawung by 36.6% and an increase in the volume of vehicles on the Jl. Pasir Kaliki is 39.3%. The increase in the volume of vehicles causes a decrease in the average speed of vehicles on the Jl. Kebon Kawung by 2% and a decrease in the average speed of vehicles on the Jl. Pasir Kaliki by 8%. So that traffic management is needed such as managing the surrounding conditions to reduce side resistances, or by widening each road segment. The results show that there is an increase in the average speed of vehicles on the Jl. Kebon Kawung by 28% and an increase in the average speed of vehicles on the Jl. Pasir Kaliki by 10%. In addition to traffic analysis on roads, an analysis of the movement of the accessible hub infrastructure itself is also carried out. The results show that the design of the building that has been designed can accommodate the estimated accessible hub passengers for the operational period (5 years).